The Impact of Polygamy on Family Harmony (Study in Gampong Lot Kala, Central Aceh Regency) - Afif Fadhil; Soraya Devy; Aulil Amri (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
Polygamy is a man who has more than one wife. In Islamic law, polygamy is a process of leadership of a man or husband in his household. If a polygamous husband is unable to implement the principle of justice in the household, he may not be able to implement justice if he becomes a leader in society. Although polygamy as prescribed in Islam has good intentions, in practice it actually causes various impacts. Likewise, the practice of polygamy in Lot Kala village is interesting to study, where the practice of polygamy that occurs in the village is indicated to have not paid attention to the sharia that has regulated it. Therefore, this study contains a study of the impacts that arise and indications of household disharmony after polygamy occurs. This study uses a case study approach, with a qualitative research type. The main data source in qualitative research comes from primary data and secondary data, using data collection techniques with literature study and interview methods. Which research results indicate that most cases of polygamy that are carried out occur without the consent of the wife which is certainly not in accordance with Article 5 paragraph (1) of Law Number 1 of 1974 concerning Marriage concerning the requirements for polygamy, namely the consent of the wife. From all cases of polygamy, it can be seen that polygamists are less able to act fairly in various matters. Where this is not in accordance with Article 55 paragraph 2 of the Compilation of Islamic Law concerning the requirements for polygamy is the obligation to act fairly and does not reflect fair behavior as contained in the Qur'an, Surah An Nisa, verse 3. Various impacts arise in polygamous families, especially negative impacts that are more dominant, giving rise to various new problems, so that the practice of polygamy clearly affects household harmony.